2018
DOI: 10.1108/aeat-01-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a pitching and plunging wing

Abstract: Purpose The complex flow behavior over an oscillating aerodynamic body, e.g. a helicopter rotor blade, a rotating wind turbine blade or the wing of a maneuvering airplane involves combinations of pitching and plunging motions. As the parameters of the problem (Re, St and phase difference between these two motions) vary, a quasi-steady analysis fails to provide realistic results for the aerodynamic response of the moving body, whereas this study aims to provide reliable experimental data. Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They showed that increasing maximum pitch angle, increases drag significantly more than lift during the pitch-up phase and the evolution of aerodynamic parameters is a function of time and maximum pitch angle, but independent of hold duration. Gkiolas et al (2018) using flow visualization techniques and pressure measurement studied the flow separation of a pitching and plunging wing.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that increasing maximum pitch angle, increases drag significantly more than lift during the pitch-up phase and the evolution of aerodynamic parameters is a function of time and maximum pitch angle, but independent of hold duration. Gkiolas et al (2018) using flow visualization techniques and pressure measurement studied the flow separation of a pitching and plunging wing.…”
Section: Introductionmentioning
confidence: 99%